Patient-reported perspectives of therapeutic radiographers when undergoing radiotherapy: A European multi-centre study. (May 2023) - O'Neill, A.G.M.; Hughes, C.M.; McClure, P.; Barbosa, B.; Muscat, K.; Oliveira, C.; Soares, A.L.; McFadden, S.
Abstract: Introduction: Radiotherapy is delivered almost exclusively by therapeutic radiographers/radiation therapist (RTTs). Patient's perspectives of RTTs affect levels of trust and confidence in the profession and can have a significant impact on overall radiotherapy experience. The study reports patients' perspectives of RTTs from their experience of undergoing radiotherapy. Four partner sites collaborated in this research and included Malta, Poland, Portugal, and the UK (lead site). Methods: A survey was developed to gather information from patients receiving radiotherapy or who had had radiotherapy within the previous 24 months. Participants ranked their responses to 23 statements relating to person-centred care on a 5-point scale of 1 (strongly disagree) to 5 (strongly agree). Mann–Whitney or Kruskal Wallis tests were applied to test differences in responses to 5 key statements for patient characteristics including gender, age group, diagnosis, country, time spent with RTTs and number of fractions remaining at survey completion. Results: Three hundred and forty-seven surveys are included. Patients report a positive perception of RTTs (95.4% agree with 'I feel cared for'). Statistically significant differences in responses were found between gender, diagnosis, country, time spent with RTTs and fractions of radiotherapy remaining. Patients who had more time with RTTs and completed their surveys during radiotherapy had a more positive perception of RTTs. Conclusion: This study suggests that sufficient time with RTTs is key to ensuring a positive radiotherapy patient experience. RTTs being attentive, understanding, and informative are most predictive of a positive overall patient experience. Timing of survey completion can influence responses. Implications for practice. RTT education programmes should incorporate training on person-centred care at all levels. Further research into patient experience of RTTs is warranted.